2022
DOI: 10.1039/d1fo04152e
|View full text |Cite
|
Sign up to set email alerts
|

A water soluble extract of radish greens ameliorates high fat diet-induced obesity in mice and inhibits adipogenesis in preadipocytes

Abstract: Radish (Raphanus sativus L.) is used for dietary source and its greens have reported functionalities. This study aimed to investigate the effects of a water-soluble extract from radish greens (WERG)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…6-, 8-, 10-gingerol and 6-, 8-and 10-shogaol, could decrease the lipid content in both 3T3-L1 cells undergoing adipogenic differentiation and in mature adipocytes derived from this cell line. Several studies evaluated the ability of plant-derived extracts to reduce the lipid content in the 3T3-L1 cell line (8,(23)(24)(25)(26). These phenols were evaluated individually in different experimental models that support their antitumor (27,28), anti-inflammatory (29,30) and anti-obesogenic capacities (31).…”
Section: Discussionmentioning
confidence: 99%
“…6-, 8-, 10-gingerol and 6-, 8-and 10-shogaol, could decrease the lipid content in both 3T3-L1 cells undergoing adipogenic differentiation and in mature adipocytes derived from this cell line. Several studies evaluated the ability of plant-derived extracts to reduce the lipid content in the 3T3-L1 cell line (8,(23)(24)(25)(26). These phenols were evaluated individually in different experimental models that support their antitumor (27,28), anti-inflammatory (29,30) and anti-obesogenic capacities (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, their limited harvest season and lack of commercialization have hindered them from being traditional specialty foods. A previous study showed that a water-soluble radish green extract reduces body fat and improves the gut environment in mice [ 3 ].…”
Section: Introductionmentioning
confidence: 99%